Nigeria yellow pages - Yell Publishers Ltd. (Abuja, Nigeria : Yell Publishers ltd., 2008)
A directory offering a listing and business information of both private and government business enterprises in some cities in Nigeria.
Includes index.
oif 23/10/14
Ref.
Keywords: Nigeria -- Directories; Government agencies -- Nigeria; Business enterprises -- Nigeria -- Directories; Directories